2017
DOI: 10.1371/journal.pone.0175692
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis and dissection of panicle components in rice using advanced backcross populations derived from Oryza Sativa cultivars HR1128 and ‘Nipponbare’

Abstract: Panicle traits are among the most important agronomic characters which directly relate to yield in rice. Grain number (GN), panicle length (PL), primary branch number (PBN), and secondary branch number (SBN) are the major components of rice panicle structure, and are all controlled by quantitative trait loci (QTLs). In our research, four advanced backcross overlapping populations (BIL152, BIL196a, BIL196b, and BIL196b-156) carrying introgressed segments from chromosome 6 were derived from an indica/japonica cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
(35 reference statements)
2
10
0
Order By: Relevance
“…Even, the relationship between the PBN vs SBL and PBN vs GN per SB showed a negative correlation. This result was in line with that reported by Sun et al (2017), where all populations being studied showed the striking positive correlations among the panicle length, grains number per panicle, primary panicle branch, and secondary panicle branch, but there was still no report about the other panicle branching traits. Bagheri et al (2011) and Norain et al (2014) reinforced the statement that there was a high significant and positive correlation between the number of grains per panicle and panicle length.…”
Section: Resultssupporting
confidence: 91%
“…Even, the relationship between the PBN vs SBL and PBN vs GN per SB showed a negative correlation. This result was in line with that reported by Sun et al (2017), where all populations being studied showed the striking positive correlations among the panicle length, grains number per panicle, primary panicle branch, and secondary panicle branch, but there was still no report about the other panicle branching traits. Bagheri et al (2011) and Norain et al (2014) reinforced the statement that there was a high significant and positive correlation between the number of grains per panicle and panicle length.…”
Section: Resultssupporting
confidence: 91%
“…The location of qpl6‐2 identified by Kobayashi et al () and Cho et al () shared the similar region. The location of qpl6 identified by Mei et al (), Liu et al (), Guo and Hong (), Sun et al () and our group shared the nearby region at the tip of the long arm of chromosome 6, and qPL6‐2 , which we identified, exhibited a large effect on PH and GW. Moreover, the location of qPL7 ‐1 identified by Cho et al () and our group shared the nearby region at the short arm of chromosome 7.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, the interaction of genotype by genotype (G × G) and genotype by environment (G × E) contributed to the trait variation (Cho et al, ; Hittalmani et al, ; Zhang et al, ). Correlation analysis also revealed the strong relationship between PL and other agronomic traits, including panicle culm length, plant height, heading stage, secondary branch number and spikelet number per panicle, and these correlated traits are usually mapped synchronously (Dang et al, ; Guo & Hong, ; Huang et al, ; Jang et al, ; Liang, Shang, Lin, Lou, & Zhang, ; Lu et al, ; Miura et al, ; Sun et al, ; Wu et al, ; Yan et al, ; Zhang, Luo, Xu, Zhang, & Xing, ), Genetic dissection for rice plant architecture showed that the PL QTL is co‐localised with either culm length, tiller number or both (Kobayashi et al, ) and finely mapped with the same locus for spikelet number per panicle (Guo & Hong, ; Xie et al, ). However, whether the loci are in tight linkage or genes are in pleiotropy is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, a ‘domestication’ construct could be created and introduced via gene editing which would permit pre-breeders to more effectively explore wild genetics. Such a construct containing key domestication loci (Zhu et al 2013 ; Li et al 2013 ; Sun et al 2017 ) could reduce the phenotypic noise in mapping populations, enhance the ability to introgress discovered genes/QTL, and reduce the generation time for creating and evaluating populations.…”
Section: Future Possibilitiesmentioning
confidence: 99%